Seroprevalence, Isolation, Genotyping, and Pathogenicity of Toxoplasma gondii Strains from Sheep in China - Yang, YuRong; Feng, YongJie; Yao, QiuXia; Wang, YingHua; Lu, YaoYao; Liang, HongDe; Zhu, XingQuan; Zhang, LongXian (Frontiers in Microbiology, 2017)
Toxoplasma gondii is an important cause of reproductive failure in small ruminants that also poses a risk to consumers who consume undercooked meat. However, little is known about sheep toxoplasmosis in China for the world. Therefore, this study was conducted to assess the prevalence of T. gondii infection in sheep from China, to isolate T. gondii via bioassay in mice and to evaluate the virulence of the isolated T. gondii based on vero cell invasion and mice. A total of 840 samples (304 unfrozen hearts and 536 sera) from sheep in China were collected from 2014-2016. Heart samples (n=36) of T. gondii seropositive sheep (MAT, ≥25) were bioassayed in mice individually. DNA derived from cell cultured tachyzoites of the isolated T. gondii was characterized by PCR-RFLP of 10 loci (SAG1, SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1, and Apico). The virulence of the T. gondii was evaluated based on the mortality and encystation in mice, as well as their growth characteristics in cell culture. Antibodies to T. gondii were found in 174 of 840 (20.71%, 304 hearts juice and 536 sera) sheep by the modified agglutination test (cut-off 1:25). Viable T. gondii was isolated from the hearts of two of 36 seropositive sheep hearts. Both genotypes of the sheep heart isolates were ToxoDB#9. The virulence of the two ToxoDB#9 isolations varied significantly. To the best of our knowledge, this is the first report of isolation of ToxoDB#9 strain of T. gondii from sheep in China.